Anomalous loss behavior in a single-component Fermi gas close to a p-wave Feshbach resonance - Welz, Kilian; Gerken, Manuel; Zhu, B.; Lippi, Eleonora; Rautenberg, Michael; Chomaz, Lauriane; Weidemüller, Matthias (Physical review, 2023)
We theoretically investigate three-body losses in a single-component Fermi gas near a p-wave Feshbach resonance in the interacting, nonunitary regime. We extend the cascade model introduced by Waseem et al. [M. Waseem, J. Yoshida, T. Saito, and T. Mukaiyama, Phys. Rev. A 99, 052704 (2019)] to describe the elastic and inelastic collision processes. We find that the loss behavior exhibits a n3 and an anomalous n2 density dependence for a ratio of elastic-to-inelastic collision rate larger and smaller than 1, respectively. The corresponding evolutions of the energy distribution show collisional cooling or evolution toward low-energetic nonthermalized steady states, respectively. These findings are particularly relevant for understanding atom loss and the energetic evolution of ultracold gases of fermionic lithium atoms in their ground state.
Gesehen am 28.06.2023